Consolidated drained behaviour of PVA fibre reinforced cemented Toyoura Sand. Issue 6 (3rd July 2022) - Safdar, Muhammad; Newson, Tim; Schmidt, Colin; Sato, Kenichi; Fujikawa, Takuro
ABSTRACT: In this study, a series of consolidated drained (CID) compression tests were performed On unreinforced and reinforced cemented Toyoura sand specimens. Specimens were cured for 3, 7, 14, 28, 56 days, with cement contents of 0–3% (dry weight), and different Polyvinyl alcohol (PVA) fibre contents of 0, 0.5, 1, 2, and 3% (weight ratio). Samples were prepared to a target dry density value (e.g. ρ d = 1.489 g/cm 3 ) of Toyoura sand using under-compaction moist tamping technique with 10% water content by dry weight of soil. Triaxial compression tests (CID) were carried out at a confining pressure of 100 kPa. The monotonic stress–strain, stiffness, volumetric change behaviour, dilatancy angle, peak strength, and residual strength and brittleness index of the samples were investigated in greater detail. Results show that peak strength increases due to increase in curing duration by approximately 50–700%, and 0–300% in residual strength at 30% axial strain, compared to Toyoura sand. For reinforced cemented specimens there is an increase in volumetric strain with increasing curing duration or in other words, the rate of dilation increases with the increase in curing period. The dilatancy behaviour increases due to the addition of fibres and cement, this dilative behaviour has been attributed to cemented particles forming highly interlocked clusters. Brittleness of the cemented specimens reinforced with 0.5%-1% fibres have been supressed significantly compared to the higher concentrations of fibre (2–3%). Hence, it shows that there might be a threshold fibre concentration range (0.5%-1%), where fibres are considered to be the most effective and beyond this concentration, fibre causes further adverse effects.